The SIMTRON concept - Ettenberg, M.; Friz, W. (IEEE transactions on electron devices, 1992)
A theory for a novel form of a high-frequency amplifier which is suitable for realization in a vacuum microelectronics structure is presented. The cathode is a linear array of field emitters or a linear ridge emitter. The RF structure is a coplanar waveguide (CPW) which may be fabricated by planar techniques. The CPW is a TEM transmission line, and the interaction may be regarded as an extended triode with spatial variation according to the wavelength; hence, the name SIMTRON (spatial injection modulation of the electrons). In the SIMTRON the parallel conductance per unit length of the TEM line is modified by the conductance of the electron beam in the interaction region. Because the beam conductance has a negative region in the neighborhood of a transit angle of one-and-a-quarter RF periods, amplification at that frequency range is possible. A numerical design example is presented for the SIMTRON.< >